Communicating for success - Hyden, Janet S.
This practical, hands-on text/CD builds on the engaging approach of learning by discovery as it guides students through the basics of developing effective workplace communication skills. The interactive project-based instruction includes practice exercises, projects, teamwork activities, career connections, Internet usage, and much more. Users will learn-by-doing as they are challenged with relevant and practical applications. Key topics include communicating at work, giving instructions, describing a mechanism and a process, applying for a job, writing letters and memos, giving reports, persuading, summarizing, interviewing for information, and listening effectively. The Data CD, included with every text, contains various formats of popular letter sytles and forms for completing projects in the book. In this revised edition, the Data CD also contains the Audio Files